PENGARUH INFLASI, BI RATE, KURS USD, DAN HARGA EMAS TERHADAP IHSG: SEBELUM DAN PASCA WABAH COVID-19 DI INDONESIA - Abdi, Muhammad; Apriyansyah Siregar, Fahmi; Sihombing, Runggu; Nasra Sinulingga, Sam Deva; Fitrawaty, Fitrawaty (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
IHSG covers all stock prices listed on the stock exchange. IHSG is calculated from the stock prices of all issuers listed on the IDX and serves as a reference for investors to observe the condition of the Indonesian capital market and make the right investment decisions. Several factors that are considered to have an influence on the movement of IHSG include inflation, interest rates (BI Rate), exchange rates (exchange rates), and commodity prices such as gold.The aim of this research to determine the influence of inflation, BI Rate, USD exchange rate, and gold price on the Jakarta Composite Index (JCI) before and after the COVID-19 pandemic in Indonesia. This study employs a quantitative approach and gathers data through literature review methods. The data, sourced from institutions like Bank Indonesia (BI) and the Central Statistics Agency (BPS), spans from 2018 to 2022 and consists of time series data. To analyze the data, the researchers use multiple linear regression methods, incorporating tests such as the coefficient of determination, the F-test, and the t-test to validate the research hypothesis. The findings suggest that inflation had no significant effect on the JCI prior to the pandemic but had a positive and significant effect after the outbreak. Interest rates (BI Rate) were found to have a positive and significant impact before the pandemic but a negative and significant impact post-pandemic. The USD exchange rate had a negative and significant effect both before and after the outbreak, while the gold price had a negative and significant effect before the pandemic but showed no significant impact after the pandemic. Collectively, these four variables were found to simultaneously affect the JCI both before and after the COVID-19 outbreak